Analysis of Accident-Prone Areas in Bekasi City - Fikri Ramdani; Widodo Budi Dermawan; Muhammad Isradi; Amar Mufhidin; Joewono Prasetijo (Journal of World Conference (JWC), 2021)
The most highlighted transportation problem at this time is traffic safety. In Bekasi City, traffic accidents often occur, ranging from minor accidents, serious accidents to accidents that cause casualties due to various factors. The objectives of this study are: To determine the characteristics of accident-prone areas, the factors causing accidents and to analyze the locations where accidents often occur in those areas. The location of this research was conducted on Jalan Raya Narogong Bekasi City. The data used in this study are primary data and secondary data. The primary data used includes the volume of passing vehicles, vehicle speed, is the road geometry, namely the absence of road markings, road capacity, land use and traffic signs.The author divides 10 segments on this road based on coordinate points. The coordinate point with the highest AEK and EPDO values ??is at the coordinate point-6.280222 to -6.28175 with AEK 103 and EPDO also 103 which caused 8 deaths, 0 serious injuries, 0 minor injuries and with material loss of Rp. 5,000,000. The most types of accidents are front - front with 17 victims, the number of accident victims and material losses is obtained from IRSMS data provided by Bekasi City traffic officers.